2021
DOI: 10.3390/polym13050784
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Effect on Dynamic Electromechanical Properties of Polyacrylic Dielectric Elastomer: An Experimental Study

Abstract: In this research, by utilizing the Very-High-Bond (VHB) 4905 elastomer, we carry out an experimental examination on the humidity effect on dynamic electromechanical performances of dielectric elastomers, including the dynamic response and viscoelastic creeping. Firstly, we experimentally analyze effects of the pre-stretch, peak voltage, waveform and frequency of the dynamic response of VHB 4905 elastomer under several ambient humidities. In general, the amplitude of dynamic deformation gradually adds up with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Based on the results, this simplification seems appropriate. Furthermore, silicone, as a membrane material, has high stability against temperature and humidity [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, this simplification seems appropriate. Furthermore, silicone, as a membrane material, has high stability against temperature and humidity [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Early claims [35,168] suggested that creep would not significantly affect most applications, though more recent studies suggest that viscoelastic behavior can degrade motion performance [170] and cause energy loss [171]. In terms of environmental tolerance, manufacturer [172][173][174], increases current leakage [58], and decreases the dielectric breakdown strength of VHB 4910 [175] so that it can be exploited in humidity sensor applications [58]. Similar effects on dielectric breakdown strength were reported for silicone elastomers, though not to the same extent as acrylic [175].…”
Section: Other Limitationsmentioning
confidence: 99%